Construction of a Model of Nurse Engagement in Long-Term Care Facilities: A Moderated-Mediation Model - Jiang, Menglin; Zeng, Jing; Chen, Xiaofang; Rao, Qian; Liao, Mingshu (Frontiers in Psychology, 2022)
Aim The aim of the study is to test a moderated mediation model that focuses on job resources mediating the relationship between organizational climate and nurse engagement in the long-term care facilities and emotional intelligence moderates this mediated relationship. Background The shortage of nurses is a global problem, especially in the long-term care facilities. We integrated and extended past research exploring the influence of nurse engagement and constructed a model of nurse engagement in the long-term care facilities. Method A cross-sectional survey was conducted on 494 nurses in long-term care facilities. Nurses were asked to complete a survey of nurse engagement, organizational climate, job resources, and emotional intelligence. Results The consequence demonstrated that organizational climate increased nurse engagement directly and indirectly via job resources. In addition, emotional intelligence plays a moderation role between organizational climate and job resources. Conclusion These phenomena revealed that a good organizational climate and job resources enable nurses to be more engaged in work. Nurse with high-emotional intelligence can take advantage of resources and improve their engagement.